Sudden death of a swimmer in water caused by heterotopic intracranial ossification and anomaly of the skull base - Pilija Vladimir; Budakov Branislav; Gvozdenović Ljiljana; Savović Slobodan; Mihalj Marija (Vojnosanitetski Pregled, 2011)
Background. Expression of immersion syndrome implies sudden and unexpected death of swimmer in water. A drowned swimmer is still a riddle for the forensic and clinical doctors. Pathophysiological mechanisms which cause immersion syndrome may be divided into vegetatively regulating and mechanical ones. Case report. We presented heterotopic intracranial ossification with the anomaly of the skull base bones development in a young man, a swimmer, drowned after entering water and where the circumstances required expertise in forensic medicine. Conclusion. Intracranial heterotopic ossification with or without a disorder in the development of skull bones may be one of the causes of immersion syndrome.